2010
DOI: 10.1371/journal.pcbi.1001021
|View full text |Cite
|
Sign up to set email alerts
|

Little Italy: An Agent-Based Approach to the Estimation of Contact Patterns- Fitting Predicted Matrices to Serological Data

Abstract: Knowledge of social contact patterns still represents the most critical step for understanding the spread of directly transmitted infections. Data on social contact patterns are, however, expensive to obtain. A major issue is then whether the simulation of synthetic societies might be helpful to reliably reconstruct such data. In this paper, we compute a variety of synthetic age-specific contact matrices through simulation of a simple individual-based model (IBM). The model is informed by Italian Time Use data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
91
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
5

Relationship

3
7

Authors

Journals

citations
Cited by 81 publications
(98 citation statements)
references
References 34 publications
6
91
1
Order By: Relevance
“…Actual mixing patterns may change significantly over time, following changes in socio-demographic characteristics [37,47] (e.g. household size and composition, characteristics of the educational system, school attendance levels).…”
Section: Discussionmentioning
confidence: 99%
“…Actual mixing patterns may change significantly over time, following changes in socio-demographic characteristics [37,47] (e.g. household size and composition, characteristics of the educational system, school attendance levels).…”
Section: Discussionmentioning
confidence: 99%
“…Two studies have compared contact patterns predicted by synthetic population modelling with observed patterns. The ‘Little Italy’ study [91] found a good comparison between the model’s age-based mixing patterns and Italian contact patterns measured by the POLYMOD study [60]. Yang et al .…”
Section: Inferring Contact Patterns From Secondary Data Analysismentioning
confidence: 99%
“…Accounting for the time spent by individuals of different ages in different social contexts and employment types allows us to mimic the complex heterogeneous mixing of individuals within the population. Similar approaches have already been proposed, for instance in562132 for studying airborne-transmitted diseases (like smallpox and influenza) and for deriving synthetic contact matrices by age. Such a high level of detail allows us to disentangle the contribution of the distinct social settings in the spread of the 2009 influenza pandemic.…”
mentioning
confidence: 96%